Regulatory strategies limiting endosomal Toll‐like receptor activation in B cells. Issue 1 (17th January 2022) - Acharya, Mridu; Jackson, Shaun W.
Abstract: The recognition of pathogen‐associated nucleic acid (NA) promotes effective immunity against invading pathogens. However, endosomal Toll‐like receptor (TLR) activation by self‐NA also underlies the pathogenesis of systemic autoimmune diseases, such as systemic lupus erythematosus (SLE). For this reason, the activation thresholds of NA‐sensing TLRs must be tightly regulated to balance protective and pathogenic immune responses. In this study, we will provide an overview of the evolutionary mechanisms designed to limit the aberrant activation of endosomal TLRs by self‐ligands, focusing on four broad strategies. These include the following: 1) the production of nucleases able to degrade self‐DNA and RNA; 2) the cell‐specific regulation of endosomal TLR expression; 3) the spatial and temporal control of TLR positioning at a sub‐cellular level; and 4) the modulation of downstream TLR signaling cascades. Given the critical role of B cells in lupus pathogenesis, where possible, we will describe evidence for B cell‐specific induction of these regulatory mechanisms. We will also highlight our own work showing how modulation of B cell endolysosomal flux tunes NA‐sensing TLR activation signals. In the face of inevitable generation of self‐NA during normal cellular turnover, these parallel mechanisms are vital to protect against pathogenic inflammation.